2019
DOI: 10.1093/mnras/stz3442
|View full text |Cite
|
Sign up to set email alerts
|

Testing the accuracy of halo occupation distribution modelling using hydrodynamic simulations

Abstract: Halo models provide a simple and computationally inexpensive way to investigate the connection between galaxies and their dark matter haloes. However, these models rely on the assumption that the role of baryons can be easily parametrized in the modelling procedure. We aim to examine the ability of halo occupation distribution (HOD) modelling to reproduce the galaxy clustering found in two different hydrodynamic simulations, Illustris and EAGLE. For each simulation, we measure several galaxy clustering statist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 94 publications
(137 reference statements)
2
29
0
Order By: Relevance
“…As such, our technique has a stronger physical motivation, as real QSOs are characterised by a high BH accretion rate and strong clustering. Thus, unlike in Sorini et al (2018), our method provides a good match to the observed QSO clustering properties (White et al 2012) without assuming a purely mass-based HOD, which can be simplistic (Beltz-Mohrmann et al 2020;Hadzhiyska et al 2020). At the same time, the number of haloes that we select is the same that we would have selected if we had simply considered all haloes with mass above M min .…”
Section: Selection Of Qsos In Smentioning
confidence: 99%
“…As such, our technique has a stronger physical motivation, as real QSOs are characterised by a high BH accretion rate and strong clustering. Thus, unlike in Sorini et al (2018), our method provides a good match to the observed QSO clustering properties (White et al 2012) without assuming a purely mass-based HOD, which can be simplistic (Beltz-Mohrmann et al 2020;Hadzhiyska et al 2020). At the same time, the number of haloes that we select is the same that we would have selected if we had simply considered all haloes with mass above M min .…”
Section: Selection Of Qsos In Smentioning
confidence: 99%
“…The process of generating multiple mock catalogues in large volumes is very efficient and can thus satisfy the demanding requirements of next-generation experiments. Unfortunately, the simplest versions of such empirical approaches have been shown to make predictions that have significant discrepancies with observations and more detailed galaxy formation models (Croton et al 2007;Paranjape et al 2015;Beltz-Mohrmann et al 2020). For example, several recent works have argued that including secondary HOD parameters, such as the local halo environment and concentration, yields better agreement with hydrodynamical simulations as compared to the standard prescription (Hadzhiyska et al 2020;Xu & Zheng 2020;Hadzhiyska et al 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…The TNG300 run followed the dynamical evolution of 2500 3 dark matter (DM) particles of mass 4.0 × 10 7 ℎ −1 M and (initially) 2500 3 gas cells of mass 7.6 × 10 6 ℎ −1 M . This box is a useful tool for galaxy formation and clustering science that has proven capable of reproducing a number of observational measurements (see, e.g., Springel et al 2018;Pillepich et al 2018a;Bose et al 2019;Beltz-Mohrmann et al 2020;Contreras et al 2020a;Gu et al 2020;Hadzhiyska et al 2020b;Montero-Dorta et al 2020b;Shi et al 2020;Hadzhiyska et al 2021;Montero-Dorta et al 2021a,b;Favole et al 2021).…”
Section: The Illustris-tng Datamentioning
confidence: 99%